Legionella longbeachae infection in a persistent hand‐wound after a gardening accident. Issue 4 (December 2014) - Mentula, Silja; Pentikäinen, Jaana; Perola, Outi; Ruotsalainen, Eija
Abstract : Introduction: Unlike other Legionella species, Legionella longbeachae has been associated with soil and potting composts instead of water systems, and it has caused pneumonia in gardeners. Case presentation: We report, to our knowledge, the first case of prolonged localized L. longbeachae infection in an accidental wound on the back of a hand caused by a broken flowerpot. Conclusion: Identification of L. longbeachae requires awareness and expertise, since commercial tests are most often specific for L. pneumophila .